The Kacchā-Pakkā Divide: Material, Space and Architecture in the Military Cantonments of British India (1765-1889) - Christopher Cowell (ABE Journal)
This article will trace the historical passage of two fundamental Indian terms used in building: kacchā (inferior, flimsy, impermanent) and pakkā (superior, solid, durable), and how they became pivotal, conjoined concepts in the construction of the military- then civil-built environments of colonial India during the period under the governance of the Honourable East India Company (1757-1858). This journey is best illustrated in the construction of the Company’s army “cantonments” or permanent garrison camps. Truly original yet overlooked inventions of eighteenth-century colonial militarism in the subcontinent—with many growing into significant urban centers by the 19th century—these stations architecturally evolved from exclusively pakkā forms to arrangements significantly shaped by kacchā work. The article will look at how and why this came about.Permitted through an expansion yet clarity in the spatial organization of the army, kacchā and pakkā work began to be blended and graded, allowing a flexibility of responses to conditions. Such responsive practices helped the three presidency armies of Bengal, Madras and Bombay to observe, build and shape modern India. Nevertheless, once applied outside of their own operations, a more rigid dichotomy emerged. As civilian populations grew against cantonments, and municipal regulations began to dictate the terms of this integration, it was one short step from identifying army-built infrastructure as either kacchā or pakkā on military maps to dividing Indian society along similar lines.